Al-Qur'anic Signals Regarding Community-Based Islamic Education Approaches: Analysis of the Concepts of Yad'ûna and Ya'murûna - Armita, Pipin; Zaitun, Z; Ahmad, Iftikhar (Multicultural Islamic Education Review, 2024)
In the Qur'an, there are various sources of knowledge, which explain various aspects of life, including education. This research aims to find out the signs of the Qur'an regarding community-based Islamic education so that it can be implemented in the Islamic education process. As for the method used in this research, because this type of research is qualitative research, the data used is from literature, that is, all the data and materials used are data or library materials that are appropriate to the problems raised. Meanwhile, the library materials used as research objects are books, journals, magazines, or other writings related to community-based Islamic education. The results of this research show that in the Qur'an two terms imply community-based Islamic education, namely the terms yad'ûna and ya'murûna. Many other terms refer to community-based Islamic education, but these two terms are directly mentioned in the Qur'an, and that is what differentiates them from other terms. Apart from that, the terms yad'ûna and ya'murûna have the meaning of calling for the implementation of God's commands. So community-based Islamic education organizers with the words yad'ûna and ya'murûna get a noble place before Allah. In the end, community-based Islamic education is an effort that brings good luck in this world and the hereafter.